Profiling of CYP4Z1 and CYP1B1 expression in bladder cancers - Yousef M. Al-saraireh (Nature Portfolio, 2021)
Abstract Bladder cancer is the tenth most common cancer worldwide, where its burden remains a challenge and needs new novel therapies. Several reports indicate expression of CYP4Z1 and CYP1B1 in many tumours. Their expressions are associated with a poor prognosis, and therefore proposed as promising biomarkers or targets for anticancer therapy. By using immunohistochemistry, expression of CYP4Z1 and CYP1B1 was evaluated in a panel of different types of bladder cancer, and the enzymes’ relation to histopathological features were assessed. Results showed an increased expression of CYP4Z1 (54.3%) and CYP1B1 (76.9%) in the majority of bladder cancers compared to weak or lack of expression of both enzymes in normal tissues. CYP4Z1expression was significantly associated with tumour grade and stage where the expression was markedly increased in a high grade and advanced stage of the disease (p < 0.05). Additionally, CYP1B1 expression was also associated with TNM staging (p < 0.05) and its expression was increased in patients with lymph node metastasis. The expression profiles of CYP4Z1 and CYP1B1 suggest that both enzymes have the potential to be biomarkers or targets for novel anticancer therapy for bladder cancer. Nevertheless, further studies are needed to better delineate whether these enzymes are druggable targets.